A Keynesian perspective on the health economics of kidney transplantation would strengthen the value of the whole organ donation and transplantation service - Leonardis, Francesca; Gitto, Lara; Favi, Evaldo; Oliva, Angelo; Angelico, Roberta; Mitterhofer, Annapaola; Cacciola, Irene; Santoro, Domenico; Manzia, Tommaso Maria; Tisone, Giuseppe; Cacciola, Roberto (Frontiers in Public Health, 2023)
Background: In this study, the Keynesian principle “savings may be used as investments in resources” is applied to Kidney Transplantation (KT), contextualizing the whole Organs Donation and Transplantation (ODT) service as a unique healthcare entity. Our aim was to define the financial resources that may be acquired in the form of savings from the KT activity. Methods: We analysed registry and funding data for ODT in our region, between 2015 and 2019. Our hypotheses aimed to evaluate whether the savings would offset the OD costs, defining the scope for growth, and estimating what savings could be generated by higher KT activity. To facilitate the evaluation of the resources produced by KT we defined a coefficient generated from the combination of clinical outcomes, activity, and costs. Results: The ODT activity reached a peak in 2017, declining through 2018-2019. The savings matured in 2019 from the KT activity exceeded €15 million while the OD costs were less than €9 million. The regional KT activity was superior to national average but inferior to international benchmarks. The estimated higher KT activity would produce savings between €16 and 20 million. Conclusions: The financial resources produced by KT contribute in defining a comprehensive perspective of the ODT finance. The optimization of the funding process may lead to the financial self-sufficiency of the ODT service. The reproducible coefficient allows reliable estimate of savings, subsequently enabling adequate investments and budgeting. Applying such perspective jointly with reliable estimate would establish the basis for an in-hospital fee-for-value funding methodology for ODT.